Transition Metals in a Cast‐Monocrystalline Silicon Ingot Studied by Silicon Nitride Gettering. Issue 12 (18th September 2019) - Sun, Chang; Liu, AnYao; Samadi, Aref; Chan, Catherine; Ciesla, Alison; Macdonald, Daniel
Abstract : The concentrations of Cr, Fe, Ni, and Cu in a cast‐monocrystalline silicon ingot grown for solar cell applications are reported. Wafers taken from along the ingot are coated with silicon nitride films and annealed, causing mobile impurities to be gettered to the films. Secondary ion mass spectrometry is applied to measure the metal content in the silicon nitride films. The bulk concentrations of the gettered metals in samples along the ingot are found to be: Cr (3.3 × 10 10 –3.3 × 10 11 cm −3 ), Fe (3.2 × 10 11 –2.5 × 10 12 cm −3 ), Ni (1.5 × 10 12 –1.3 × 10 13 cm −3 ), and Cu (7.1 × 10 11 –3.2 × 10 13 cm −3 ). For each metal, the lower limit is measured on the wafer from the middle of the ingot, and the higher limit is measured on wafers from the bottom or the top. The results are compared with similar data recently measured on a high‐performance multicrystalline silicon ingot. The results provide insights into the total bulk concentrations of the metals in cast‐grown ingots. Abstract : The concentrations of Cr, Fe, Ni, and Cu in a cast‐monocrystalline silicon ingot grown for solar cell applications are reported. Wafers from along the ingot are coated with silicon nitride films, and annealed, to concentrate the impurities in the bulk into the films. The concentrated impurities are then measured by secondary ion mass spectrometry.